2021
DOI: 10.3390/cells11010029
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Angiotensin-Converting Enzyme and Apolipoproteins Are Associated with Alzheimer’s Disease and Cardiovascular Diseases

Abstract: Angiotensin-converting enzyme-1 (ACE1) and apolipoproteins (APOs) may play important roles in the development of Alzheimer’s disease (AD) and cardiovascular diseases (CVDs). This study aimed to examine the associations of AD, CVD, and endocrine-metabolic diseases (EMDs) with the levels of ACE1 and 9 APO proteins (ApoAI, ApoAII, ApoAIV, ApoB, ApoCI, ApoCIII, ApoD, ApoE, and ApoH). Non-Hispanic white individuals including 109 patients with AD, 356 mild cognitive impairment (MCI), 373 CVD, 198 EMD and controls we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
(74 reference statements)
1
4
0
Order By: Relevance
“…We found rs7412-T is significantly associated with lower Apolipoprotein B (apoB), Lipoprotein A, LDL, total cholesterol, and lower risk of lipoprotein metabolism disorder (ICD10: E78) across ancestries with concordant effects. This is consistent with published evidence of rs7412-T association with lipid biomarkers in Europeans, Africans, Asians, and Hispanics 2836 ; lower apoB has been linked to reduced AD risk, with causality to be confirmed 32,3743 . As expected, rs429358-C, is associated with higher risk of dementia and cognitive disorders (F01-F09), intracranial hemorrhage and cerebrovascular disease (ICD10: I60-I69).…”
Section: Resultssupporting
confidence: 91%
“…We found rs7412-T is significantly associated with lower Apolipoprotein B (apoB), Lipoprotein A, LDL, total cholesterol, and lower risk of lipoprotein metabolism disorder (ICD10: E78) across ancestries with concordant effects. This is consistent with published evidence of rs7412-T association with lipid biomarkers in Europeans, Africans, Asians, and Hispanics 2836 ; lower apoB has been linked to reduced AD risk, with causality to be confirmed 32,3743 . As expected, rs429358-C, is associated with higher risk of dementia and cognitive disorders (F01-F09), intracranial hemorrhage and cerebrovascular disease (ICD10: I60-I69).…”
Section: Resultssupporting
confidence: 91%
“…It is strongly recommended to promote future research to address these existing disparities and to gain a clearer understanding of the specific function of ACE in clearing amyloid-β. Such insights could potentially prove valuable in preventing the buildup of amyloid-β in the brain, which is a characteristic feature of conditions like AD [ 82 ] and CAA [ 83 ].…”
Section: Amyloid-β Clearance In the Brainmentioning
confidence: 99%
“…A recent study reported reduced levels of apoA-II proteins (but not apoA-I) in patients with Alzheimer’s disease or mild cognitive impairment, as compared to normal cognitive individuals [ 136 ]. In addition, increased apoA-II was found in patients with endocrine-metabolic diseases, as compared to non-endocrine-metabolic diseases individuals, while no difference was found in apoA-II when patients with cardiovascular disease were compared with non-cardiovascular disease individuals [ 136 ].…”
Section: Role Of Apoa-ii In Various Pathologiesmentioning
confidence: 99%